2020
DOI: 10.3390/app10072432
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of EDM through Relief-Angled Tool Designs

Abstract: Among the family of carbides, tungsten carbide (WC) and its variants have extensive use in numerous applications including cutting tools, dies, and many wear resistant parts. Such applications need machining of WC, which is famously considered as challenging due to high tool wear mainly in traditional machining. Sinking electric discharge machining (EDM) can be considered as a suitable alternate but the low machining rate of EDM, with conventional tool design, poses limitations. In this research, the conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In this study, it has been found that non-conventional electrode design offers high MRR with low overcut as compared to the conventional electrode. In the same study, the relief angled designed tools have been reported as the better option to obtain less amount of overcut while machining circular holes in tungsten carbide [ 26 ]. To select the most appropriate electrode design offering high MRR, and low amounts of TWR and overcut, the electrode design with 20 degree can be considered as the common suitable choice.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, it has been found that non-conventional electrode design offers high MRR with low overcut as compared to the conventional electrode. In the same study, the relief angled designed tools have been reported as the better option to obtain less amount of overcut while machining circular holes in tungsten carbide [ 26 ]. To select the most appropriate electrode design offering high MRR, and low amounts of TWR and overcut, the electrode design with 20 degree can be considered as the common suitable choice.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the dimensional errors in EDM, researchers attempted to modify the electrode geometry. They employed electrodes with a certain relief angle and observed a reduction in the value of overcut [24]. Liang et al [25] proposed a self-repair method and a profile error compensation method for tool electrode wear to improve processing accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The enormous demand for tools, tooling, dies, and molds is due to the extensive use of these items in production. How likely a discharge is determined by how easily electricity can be broken down within the spark gap [4,5]. Any point between the two electrodes will experience a more severe electrical breakdown if debris is present.…”
Section: Introductionmentioning
confidence: 99%